Application of the Hungarian Method in Workforce Scheduling Optimization at the Magetan Dynamic Vegetable-Tanned Leather Sandal Industry - Nafisyatul Azizah; Putri Amelia Hanifa; Revania Eka Putri Devitasari; Rizka Tri Wahyuni; Lisnani Lisnani; Sumarni Sumarni (Program Studi Pendidikan Matematika Universitas Kuningan, 2025)
Task allocation at the Dinamis Magetan vegetable-tanned leather sandal industry is currently handled flexibly, based on workers' general availability rather than a systematic evaluation of individual processing-time efficiency, creating a risk of inconsistent completion times across its five sequential production stages. Although the Hungarian Method has been widely applied to optimize labor assignment across various Indonesian MSME sectors, its application to traditional craft industries with a flexible, multi-skilled workforce — such as vegetable-tanned leather sandal production, where workers are trained to master every stage (